Efektivitas website perguruan tinggi negeri sebagai penyedia informasi bagi mahasiswa - Kriyantono, Rachmat (Faculty of Communications Science, Dr. Soetomo University, 2020)
This study aims to describe the practice of public relations communication on the website of state universities. It explores the opinions of state university students on the website of their respective university. Evaluating websites based on student opinion is consired beneficial because the students are users who frequently access the website for administrative and academic purposes. The method used in this study was a survey with 360 respondents from four state universities in Malang. From the data findings, it can be concluded that in general, the websites of the four university have been rated effective by students based on several dimensions of website quality, such as transparency, interactivity, accessibility, useful information, web maturity, usability, openness, and positivity. However, the positivity dimension needs to be amended further because three out of four state university websites are only considered to be quite effective.